Consórcio entre alface e calêndula: Produtividade das culturas e teor de flavonóides em calendula - Fonseca, Maira Christina Marques; Sediyama, Maria Aparecida Nogueira; Bonfim, Filipe Pereira Giardini [UNESP]; das Dores, Rosana Gonçalves Rodrigues; Gonçalves, Melina Guimarães; do Prado, Adalgisa Leles; Lopes, Iza Paula de Carvalho (FapUNIFESP (SciELO), 2016)
Intercropping of vegetables and medicinal plants might produce favorable interactions for both crops, resulting in increased production and profit per unit area. It is known that active compounds can change because of several factors, including the cropping system. Therefore, the goal of this study was to evaluate the effect of intercropping of lettuce and marigold on the productivity of these crops and on the flavonoid content of marigold flowers. The experiment was conducted in the experimental area of EPAMIG in Oratorios-MG. Treatments consisted of lettuce + marigolds intercropping between rows, lettuce + marigold intercropping between plants, and monocultures of each species. Spacing was 0.3x0.3m. The experimental design consisted of randomized blocks with ten repetitions. Harvest of lettuce and marigold flowers started 45 days after transplantation (DAT) and extended up to 72 DAT for marigolds. Lettuce and marigold intercropping appears feasible because lettuce production did not differ between the monoculture and intercropped cultivations, and marigold productivity was higher when intercropped with lettuce. No change in the flavonoid (active chemicals of medicinal interest) content in the floral capitula of marigolds was observed.
Lettuce and marigold intercropping: Crops productivity and marigold’s flavonoid content
Keywords: Calendula officinalis L; Crop association; Lactuca sativa L; Land equivalent ratio; Medicinal plants